2021
DOI: 10.1155/2021/5593589
|View full text |Cite
|
Sign up to set email alerts
|

Influence of SGLT2 Inhibitor Treatment on Urine Antioxidant Status in Type 2 Diabetic Patients: A Pilot Study

Abstract: Sodium-glucose cotransporter 2 inhibitors (SGLT2i) have been recognized as potent antioxidant agents. Since SGLT2i are nephroprotective drugs, we aimed to examine the urine antioxidant status in patients with type 2 diabetes mellitus (T2DM). One hundred and one subjects participated in this study, including 37 T2DM patients treated with SGLT2i, 31 T2DM patients not using SGLT2i, and 33 healthy individuals serving as a control group. Total antioxidant capacity (TAC), superoxide dismutase (SOD), manganese supero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…However, a meta-analysis of 15 randomized and 8 observational clinical studies of these drugs showed a consistent reduction in biomarkers of both inflammation (CRP, IL-6, and TNF-α) and oxidative stress (8-iso-prostaglandin F2α and 8-hydroxy-2′-deoxyguanosine) and an increase of the cardioprotective adiponectin derived from adipose tissue [ 257 ]. In a recent real-world observational pilot trial, treatment with various SGLT2-Is modified the redox status and antioxidant enzyme activity in the urine of T2DM patients [ 258 ].…”
Section: Anti-inflammatory and Anti-oxidant Effects Of Sglt2-ismentioning
confidence: 99%
“…However, a meta-analysis of 15 randomized and 8 observational clinical studies of these drugs showed a consistent reduction in biomarkers of both inflammation (CRP, IL-6, and TNF-α) and oxidative stress (8-iso-prostaglandin F2α and 8-hydroxy-2′-deoxyguanosine) and an increase of the cardioprotective adiponectin derived from adipose tissue [ 257 ]. In a recent real-world observational pilot trial, treatment with various SGLT2-Is modified the redox status and antioxidant enzyme activity in the urine of T2DM patients [ 258 ].…”
Section: Anti-inflammatory and Anti-oxidant Effects Of Sglt2-ismentioning
confidence: 99%
“…Contrarily, Nabrdalik-Leśniak et al have described that therapy of at least one month with either canagliflozin or empagliflozin decreased total antioxidant capacity (estimated by ABTS urine levels) in diabetic patients as compared to that of diabetic patients not treated with SGLT2is and healthy controls. However, the urinary activity of the antioxidant enzymes SOD and MnSOD was increased in diabetic patients treated with SGLT2is, suggesting that these drugs can also promote the activation of antioxidant mechanisms [ 100 ]. In this line, Iannantuoni et al have described that 24-week long treatment with empagliflozin reduces superoxide production, increases glutathione content (an antioxidant), and enhances the expression of glutathione s-reductase and catalase in leukocytes of diabetic patients.…”
Section: Antioxidant Properties Of Sglt2 Inhibitorsmentioning
confidence: 99%
“…Individuals on SGLT2 inhibitors alone exhibited only decreases in 2,2¢-azino-bis-(3-ethylbenzthiazoline-6-sulphonic acid) radical after 12 months of follow-up, with no major differences being noted in the rest of the examined markers [ 88 ]. In another pilot study, SGLT2 inhibitors induced a reduction in urinary SOD and MnSOD activity, as well as in total antioxidant capacity, in individuals with type 2 diabetes mellitus [ 89 ]. The addition of SGLT2 inhibitors to angiotensin-converting enzyme inhibitor ramipril resulted in the lowering of urinary 8-isoprostane concentration compared to the addition of placebo to ramipril in the randomized, double-blind, placebo-controlled, crossover trial of Lytvyn et al [ 90 ].…”
Section: Antioxidant Pharmacotherapies In Cardiorenal Diseasesmentioning
confidence: 99%